2016
DOI: 10.3892/ol.2016.5018
|View full text |Cite
|
Sign up to set email alerts
|

TGFB2 and BCL2L11 methylation in male laryngeal cancer patients

Abstract: Abstract. DNA methylation is a major regulatory mechanism of gene expression. The aim of the present study was to test the association of transforming growth factor β2 (TGFB2) and B cell lymphoma 2-like 11 (BCL2L11) gene methylation with the risk of laryngeal squamous cell carcinoma (LSCC). Using bisulfite pyrosequencing technology, DNA methylation levels of TGFB2 promoter and BCL2L11 gene-body CpG cytosines were measured in 90 LSCC tissues and 90 adjacent normal tissues. Analysis of variance and paired sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…BCL2L11 (also known as BIM) is a member of BCL-2 family, inducing apop-tosis and inhibiting autophagy by inactivating BCL2 or by activating BAX-BAK1 and by bridging BECN1 or DYNLL1, respectively [ 25 27 ]. According to previous reports, BCL2L11 is involved in biological pro-cesses in a variety of solid tumors such as ovarian cancer, endometrial adenocarcinoma, prostate tumor and gastric cancer [ 28 – 30 ]. Cumulating evidence has demonstrated that the dysregulation of miRNAs plays crucial roles in the pathology tumorigenesis by directly tar-geting the 3′-UTRs of mRNA of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…BCL2L11 (also known as BIM) is a member of BCL-2 family, inducing apop-tosis and inhibiting autophagy by inactivating BCL2 or by activating BAX-BAK1 and by bridging BECN1 or DYNLL1, respectively [ 25 27 ]. According to previous reports, BCL2L11 is involved in biological pro-cesses in a variety of solid tumors such as ovarian cancer, endometrial adenocarcinoma, prostate tumor and gastric cancer [ 28 – 30 ]. Cumulating evidence has demonstrated that the dysregulation of miRNAs plays crucial roles in the pathology tumorigenesis by directly tar-geting the 3′-UTRs of mRNA of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…BCL2L11 (also known as BIM) is a member of BCL-2 family, inducing apop-tosis and inhibiting autophagy by inactivating BCL2 or by activating BAX-BAK1 and by bridging BECN1 or DYNLL1, respectively [42] .According to previous reports, BCL2L11 is involved in biological pro-cesses in a variety of solid tumors such as ovarian cancer, endometrial adenocarcinoma, prostate tumor and gastric cancer [43][44][45] .PAN et al' [46] data demonstrated that lncRNA ACTA2-AS1 could suppress colon adenocarcinoma progression via sponging miR-4428 to regulate BCL2L11 expression.ZHANG et al' [47] studies from both in vitro and in vivo shown that miR-24 regulates BCL2L11 expression by directly binding with 3'UTR of mRNA, thus promoting gastric cancer cell growth, migration while inhibiting cell apoptosis.YUAN et al' [48] results showed that downregulation of LncRNA H19 could promote cell proliferation, inhibit cell apoptosis, and suppress multiple in ammatory cytokine expressions in HK-2 cells by modulating the miR-130a/BCL2L11 pathway.As a disease of digestive system,IBS-D was speculated to be closely related to the above key genes QKI and BCL2L11 and PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is a highly studied epigenetic mechanism that plays an important role in regulating gene expression. As noted previously, abnormal DNA methylation can induce related diseases such as stroke [ 27 ], cardiovascular disease [ 28 ], and malignancies [ 29 ]. However, the role of DNA methylation in the pathogenesis of ischemic stroke is yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%